2008
DOI: 10.1038/nature06875
|View full text |Cite
|
Sign up to set email alerts
|

HP1-β mobilization promotes chromatin changes that initiate the DNA damage response

Abstract: Minutes after DNA damage, the variant histone H2AX is phosphorylated by protein kinases of the phosphoinositide kinase family, including ATM, ATR or DNA-PK. Phosphorylated (gamma)-H2AX-which recruits molecules that sense or signal the presence of DNA breaks, activating the response that leads to repair-is the earliest known marker of chromosomal DNA breakage. Here we identify a dynamic change in chromatin that promotes H2AX phosphorylation in mammalian cells. DNA breaks swiftly mobilize heterochromatin protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

36
421
9
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 396 publications
(468 citation statements)
references
References 26 publications
36
421
9
2
Order By: Relevance
“…One of the most compelling evidence was reported by (Loizou et al (2004), demonstrating that CK2 has a direct role in the DNA repair by phosphorylating XRCC1, thereby enabling the assembly and activity of DNA single-strand break repair at sites of chromosome breakage. The CK2-catalyzed phosphorylation of HP1-b, a chromatin factor bound to histone H3, was found to occur in cells exposed to DNA damage and this event was accompanied by HP1-bmobilization and subsequent alteration in chromatin structure (Ayoub et al, 2008). Although mounting evidence indicates that CK2 is implicated in the earliest cellular response to DNA breakage, the relationship between CK2 and components of the DNA damage response is yet to be thoroughly explored.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most compelling evidence was reported by (Loizou et al (2004), demonstrating that CK2 has a direct role in the DNA repair by phosphorylating XRCC1, thereby enabling the assembly and activity of DNA single-strand break repair at sites of chromosome breakage. The CK2-catalyzed phosphorylation of HP1-b, a chromatin factor bound to histone H3, was found to occur in cells exposed to DNA damage and this event was accompanied by HP1-bmobilization and subsequent alteration in chromatin structure (Ayoub et al, 2008). Although mounting evidence indicates that CK2 is implicated in the earliest cellular response to DNA breakage, the relationship between CK2 and components of the DNA damage response is yet to be thoroughly explored.…”
Section: Introductionmentioning
confidence: 99%
“…The latter two fusion constructs only carry the chromodomain (chromo) of CBX1 (also known as HP1beta) that is responsible for binding to the pericentromerically enriched H3K9me3 mark (Bannister et al 2001;Lachner et al 2001;Nakayama et al 2001) but lacks the hinge and chromoshadow domains that accommodate the protein-nucleic acid and most protein-protein interactions of CBX1 (Hiragami and Festenstein 2005). The threonine at position 34 in the chromodomain (position 51 in the CBX1 protein) is critical for H3K9me3 association, and binding to this heterochromatic mark is therefore disrupted in the chromo T34A mutant (Ayoub et al 2008). Concordantly, visual inspection showed that the fluorescently tagged chromo protein preferentially localized at DAPI-dense chromocenters.…”
Section: Induced Proximity To Chromocenters Is Sufficient For Transcrmentioning
confidence: 99%
“…131 Although the opposite process, which leads to the recovery of the HP1β-H3K9me interaction and the heterochromatin structure, has not been studied, this finding suggests a mechanism that would have important consequences for the maintenance of the epigenetic status. Since chromatin structure is disrupted by the modification of a histone binding protein, rather than of the histones themselves, the original histone modification pattern remains unaltered in areas around the DNA lesion.…”
Section: Restoring Chromatin Structurementioning
confidence: 97%